The learning of cultural diversity and the patrimonialization of biodiversity - José Rogério Lopes; Paolo Totaro (Ciências Sociais Unisinos)
This article discusses the phenomenological assumptions that are at the basis of a rela-tional approach between the conceptions of biodiversity and cultural diversity in the hori-zon of community experiences of the production of identity goods operating in processes of pre-patrimonialization. The scope of this discussion comprehends cases investigated in different regions of Brazil in order to recognize the various perceptions of otherness that constitute the experiences revealed through an ecological path, as well as their situational and discursive agencies. The enunciation of these agencies, in turn, takes into account that the latter are conditioned or mediated by market and institutional devices of cultural and environmental policies, such us emergent arrangements of biodiversity.